"Kartagam" media in improving readiness to read in early children - Suyatinah, Suyatinah; Mulyono, Rahmat (Gema Wiralodra, 2023)
Paying attention to children's development and the need to develop the reading potential of preschool-age children, there is something that can help achieve the goal of learning to read optimally, namely through parenting. The care used in teaching preschool-age children must pay attention to their level of development. Paying attention to the level of development means also considering their developmental tasks. The objectives to be achieved in this research are: 1) Describe the ongoing process of early reading preparation learning through letter matching activities using word and picture cards (Kartagam) in early childhood, 2) Describe the magnitude of the increase in early reading preparation through letter/word matching activities using word and picture card media (Kartagam) in early childhood, and3)Describe changes in attitudes and learning behavior of young children after early reading preparation lessons were carried out through letter matching activities using word and picture cards (Kartagam). Using the media "Kartagam" (Word and Picture Cards) is hoped to improve children's literacy skills, especially early childhood reading readiness.